Treatment of aplastic anemia by marrow transplantation from HLA identical siblings. Prognostic factors associated with graft versus host disease and survival. - Rainer Storb; Ross L. Prentice; E. Donnall Thomas (1977)
73 consecutive patients with severe aplastic anemia were treated by marrow transplantation from hematologically normal HLA identical siblings. 68 patients lived long enough to document marrow engraftment. 21 rejected the graft and 19 of these died. 47 sustained engraftment and 18 of these died. In 16 patients, death was associated with graft versus host disease. 29 patients with sustained engraftment are alive with complete hematologic restoration between 8 mo and 5 yr. This analysis, by using a proportional hazards regression model, was directed at identifying factors that predicted survival (and absence of graft versus host disease). Of the 24 factors entered into the analysis only two strongly correlated with survival: (a) sex match of donor and recipient (P less than 0.01), and (b) absence of refractoriness to random donor platelets at the time of transplantation (P less than 0.05). Refractoriness adversely influenced the survival of the sex mismatched patients, These data suggest that X and Y-associated transplantation antigen systems are important determinants of the outcome of marrow grafts between HLA identical siblings for the treatment of aplastic anemia. The machanism by which refractoriness to random donor platelets influences survival is currently unclear.